PERANAN BIAYA DISTRIBUSI DAN BIAYA PERSONAL SELLING TERHADAP PENJUALAN PADA TOKO ERA KERAMIKA PEMATANGSIANTAR - Salim, Edy; Lie, Darwin; Butarbutar, Marisi; Julyanthry, Julyanthry (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2019)
ABSTRACTThe purpose of this study is to examine and analyze 1. The Description of distribution costs, personal selling costs, and sales at Keramika Pematangsiantar Era Store. 2. The role of distribution cost and personal selling costs on sales the Pematangsiantar Era Keramika Store both simultaneously and partially.Based on the results of the analysis through the trend formlula for 1. Distribution cost, it can be interpreted that the distribution cost are interpreted that the distribution costs are positively proportional to sales, where when X is raised one unit is predicted to increase sales. The trend for 2. Personal selling costs, it means that the costs of personal selling is positively proportional to sales, where when X is raised one unit is predicted to increase sales. 3. Sales trend, it means that sales experience a monthly increase of 197.368,42. Based on the results of the analysis and evaluation of distribution cost and personal selling cost, it has a role in increasing sales at Keramika Pematangsiantar Era Store.Â Â Keyword: Distribution Cost, Personal Selling Cost, and Sales